(3LegQI GdCeKGds - (3GdMSf Hf YHO Gddg Hf Sgd Hf SYjO GHf jMji Hf egQGf GdnYrSncQj, CHh gdGd,J (B395 (3g` s
(3ChdgG (B:s
(3CMeO Gddg MeO GdTGcQjf, hCTgO HhMOGfjJg TgGOI GdYGQbjf Ke Efj deG QCjJ MGLI GdTQja Edi TF ef BOGH GddSGf HYO SdGeJg ef GddMf, cMGLJg Edi GdTGgO hGdeKd hGdTPQI hGdfGOQI s
(3BNQgG (B:s
(3CjSQ ef dbeGf Hf YGO, hcGf CVQH GdfGS HGdbOGM hGdCjSGQ(B: (3Gdbhe jLJeYhf ajVQHhf HGdbOGM, hCMOge jSQ hGdYQH Jbhd(B: (3ge cCjSGQ dbeGf Hf YGO ddbhe jchf dge TQa bGd WQaI s
(3GdfSNI HgG MhGTs
(3fSNI KGfjI s
(3Ydi ghGeTgG MhGT hJYdjbGJ cKjQIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs